Profile of Head and Neck Cancer Patients at Department of Otorhinolaringology-Head and Neck Surgery Dr. Hasan Sadikin General Hospital Bandung - Rakhmawulan, Inez Aulia; Dewi, Yussy Afriani; Nasution, Nursiah (Althea Medical Journal, 2015)
Background: Head and neck cancer is a health problem with a high mortality rate. Head and neck cancer are increasing and effect many individuals from diverse backgrounds. Usually patients come with advanced stages, therefore these conditions could lead to decrease their quality of life. Aim of this study was to describe the profile of head and neck cancer patients at the Otorhinolaringology-Head and Neck Surgery Department, Dr. Hasan Sadikin General Hospital Bandung.Methods: A descriptive cross-sectional method was used from medical records of head neck cancer patients at Department of Otorhinolaringology-Head and Neck Surgery, Dr. Hasan Sadikin General Hospital Bandung from 2008 to 2012 that used the total sampling method.Results: There were 665 patients included in this study, which men who participated were 388 and women were 277. Most of them were elementary educated (44.96%), housewives (32.03%), and those aged 46â55 years old (28.33%). There were nasopharyngeal (38.20%), sinonasal (17.29%), larnyx (13.08%), oropharnyx (6.32%), thyroid gland (6.17%), oral cavity (3.91%), hypopharynx (2.41%), and parotid gland (2.26%) cancer. The major histopathological findings were undifferentiated carcinoma (45.41%) and squamous cell carcinoma (22.26%), those were presented with stage I (7.4%), II (13.5%), III (24.4%), and IV (54.7%).Conclusions: Nasopharyngeal carcinoma was the most predominant cases which majority were presented in advanced stage and major histopathology features was undifferentiated carcinoma, while demografic characteristic mostly were in middle aged and older, men with low education background. [AMJ.2015;2(4):474â9]Â DOI:Â 10.15850/amj.v2n4.630